Case Report: Successful dupilumab treatment for refractory atopic dermatitis-like eczema in a patient with Costello syndrome - Toshihiko Nonaka; Jun Kido; Mika Ogata; Taiga Miyake; Takanobu Yoshida; Satoshi Fukushima; Rie Seyama; Yuri Uchiyama; Naomichi Matsumoto; Kimitoshi Nakamura (Journal of Cutaneous Immunology and Allergy, 2026)
Costello syndrome is a rare RASopathy caused by pathogenic variants in HRAS and is characterized by distinctive craniofacial features, growth failure, cardiac abnormalities, tumor predisposition, and various cutaneous manifestations. Although eczema has been reported in patients with Costello syndrome, reports of severe AD-like eczema accompanied by clinically significant allergic manifestations, including food allergy, remain limited. We report a female patient with Costello syndrome caused by a heterozygous HRAS variant, NM_005343.4:c.37G>T, p.(Gly13Cys), who developed severe atopic dermatitis-like eczema and hen’s egg and cow’s milk allergies from infancy. Despite treatment with topical anti-inflammatory agents and emollients, her AD-like eczema remained refractory. Add-on dupilumab therapy was initiated in adolescence, resulting in marked improvement in her skin manifestations within 1 month, and clinical improvement was maintained during subsequent follow-up. This case suggests that dupilumab may be an effective therapeutic option for refractory atopic dermatitis-like eczema associated with Costello syndrome. The clinical course also supports the possible contribution of epithelial-driven type 2 inflammation to severe allergic manifestations in Costello syndrome, although direct mechanistic evidence was not obtained.